Índices antecedentes e coincidentes da atividade econômica brasileira:uma aplicação da análise de correlação canônica - Spacov, Andrei Dudus (2001)
This paper uses canonical correlation analisys to identify leading and coincident indicators of economic activity in Brazil. ln contrast with the traditional literature on the subject, no restrictions are made regarding the number of common cycles that are necessary to explain the complete cyclical behavior of the coincident variables. For the brazillian data, it is found that three common cycles exhaust all the cyclical pattern of economic activity. Based on the methodology developed here, it is also sugested an alternative chronology of the recent brazillian recessions.